Strong latitudinal gradient in temperature-growth coupling near the treeline of the Canadian subarctic forest - Chagnon, Catherine; Moreau, Guillaume; D’Orangeville, Loïc; Caspersen, John; Labrecque-Foy, Julie-Pascale; Achim, Alexis (Frontiers in Forests and Global Change, 2023)
Boreal forests are experiencing severe climatic changes that vary widely across the broad geographic distribution of the biome. The changes are greatest near the subarctic treeline where trees often exhibit high climatic sensitivity because climatic conditions approach the limits of their physiological tolerance. Despite the importance of subarctic boreal forests, the lack of field-acquired growth data remains a critical issue that limits the generalization of forest productivity models across the entire boreal biome. Using tree-ring chronologies from remote stands distributed along three latitudinal gradients ranging from 65 to 102°W, we investigated recent trends in black spruce growth and their relationships with recent climate warming near the subarctic treeline in eastern Canada. Our results show a generally positive effect of temperature and a negative effect of precipitation, both indicating that black spruce growth is temperature-limited near its northern range limit. However, we observed a strong gradient in temperature-growth coupling within a small latitudinal gradient (about one degree of latitude), where strong temperature constraints appear limited to the northernmost, coldest stands. Moreover, the positive growth response to temperature decreased from wetter to dryer sites and climate-growth coupling declined over the study period in the driest sites. These results suggest that the growth increase associated with warmer temperature may be limited by reduced precipitation and potential moisture limitation. Lastly, our results suggest that acute climatic events have the potential to induce abrupt shifts in tree climate-growth relationships. Such results indicate that the expected beneficial effect of warming on high latitude tree growth may be less generalized and more complex than previously thought in northeastern Canada, perhaps due to factors other than temperature, which might confound the climate-growth coupling southwards. Thus, our results highlight the need for a better understanding of additional growth drivers in these poorly studied regions and for physiologically-informed definitions of acute climatic events, in order to inform broad-scale forest productivity modeling.